2022
DOI: 10.1177/00491241221122603
|View full text |Cite
|
Sign up to set email alerts
|

Machine Learning as a Model for Cultural Learning: Teaching an Algorithm What it Means to be Fat

Abstract: Public culture is a powerful source of cognitive socialization; for example, media language is full of meanings about body weight. Yet it remains unclear how individuals process meanings in public culture. We suggest that schema learning is a core mechanism by which public culture becomes personal culture. We propose that a burgeoning approach in computational text analysis – neural word embeddings – can be interpreted as a formal model for cultural learning. Embeddings allow us to empirically model schema lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 137 publications
(356 reference statements)
1
25
0
Order By: Relevance
“…On the other hand, jazz and rap projected more strongly onto the ‘black pole’ of the race dimension while opera and bluegrass projected more strongly onto the ‘white pole’. A similar approach showed that obesity‐related words carry strong ‘unhealthy’ and ‘female’ bias in New York Times articles (Arseniev‐Koehler & Foster, 2020).…”
Section: Dimensions Of Bias As Directions In Word Embeddingsmentioning
confidence: 99%
See 3 more Smart Citations
“…On the other hand, jazz and rap projected more strongly onto the ‘black pole’ of the race dimension while opera and bluegrass projected more strongly onto the ‘white pole’. A similar approach showed that obesity‐related words carry strong ‘unhealthy’ and ‘female’ bias in New York Times articles (Arseniev‐Koehler & Foster, 2020).…”
Section: Dimensions Of Bias As Directions In Word Embeddingsmentioning
confidence: 99%
“…Arseniev‐Koehler & Foster, 2020; Garg et al, 2018; Kozlowski et al, 2019; Rodman, 2020). For example, Arseniev‐Koehler and Foster (2020) found that boyish was masculine on each of 25 replications, and on every model, it was less masculine than tough_guy . Even small differences in bias can be reliably detected.…”
Section: Reliability and Validitymentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, text mining methods are only as good as we are as researchersthus, rather than replacing our efforts, they should only augment our capabilities .,Substantive research questions might even call for a combination of multiple methods that tackle different tasks in text analysis (Bonikowski and Nelson 2022). It is important to note that using data generated by individuals in their everyday life creates a particularly large gap between the raw data and meaningful measures of scientifically relevant concepts (Lazer et al 2021) and that relying on complex machine learning models carries a risk of unwillingly reproducing existing biases and cultural perceptions (Arseniev-Koehler and Foster 2022;Waseem 2016;Whittaker et al 2018).…”
Section: Conclusion and Final Remarksmentioning
confidence: 99%